Los herederos de los abuelos: Sobre la socialización religiosa en familias de diferentes credos en Buenos Aires - Zaros, Agustina Adela (2018)
This paper analyze the socialization in families belonging to differents religious traditions and living in the Metropolitan Area of Buenos Aires. The aims of this qualitative research is understand how is the transgenerational memory transmission and how the religion builds family. The theoretical approach is from the sociology of religion and the family is one of the places of the social construction of reality with the aims of understand the religious memories and experiences through owns practices. The results highlight the influence of religious ethos on family descendants, the presence of grandparents in the family’s memories and the unlineal trajectory in the transgenerational transmission of families, that include tensions between the beloging to the group and the own individuality.